TANGGUNG JAWAB RUMAH SAKIT MITRA KELUARGA KALI DERES ATAS TINDAKAN PENOLAKAN PASIEN YANG BERUJUNG PADA KEMATIAN DITINJAU DARI UNDANG-UNDANG NO.8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Andre Scondery; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2018)
The hospital is a place where a person receives health services, where the hospital is a place that does not discriminate against a person in providing health services and this has been regulated by the Hospital Law, Health Act and also the Consumer Protection Act. But in reality there are still those who perform service actions by distinguishing the case of a Deborah baby who received a different treatment by the hospital so that the baby Deborah patient died of the treatment given by the hospital. The treatment is in the form of a hospital that does not carry out social functions based on the applicable law so that this action results in death to patients. This is caused because the family of Deborous patients cannot follow the request of the hospital which requires patients to pay the amount set by the house sick so that the hospital does not carry out actions according to social functions. In this case the hospital must be responsible for the actions it has taken.